2017
DOI: 10.1371/journal.pmed.1002432
|View full text |Cite
|
Sign up to set email alerts
|

Virological response and resistance among HIV-infected children receiving long-term antiretroviral therapy without virological monitoring in Uganda and Zimbabwe: Observational analyses within the randomised ARROW trial

Abstract: BackgroundAlthough WHO recommends viral load (VL) monitoring for those on antiretroviral therapy (ART), availability in low-income countries remains limited. We investigated long-term VL and resistance in HIV-infected children managed without real-time VL monitoring.Methods and findingsIn the ARROW factorial trial, 1,206 children initiating ART in Uganda and Zimbabwe between 15 March 2007 and 18 November 2008, aged a median 6 years old, with median CD4% of 12%, were randomised to monitoring with or without 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
(29 reference statements)
4
21
0
Order By: Relevance
“…Our ndings are in agreement with previous Sub-Saharan Africa studies which have shown that clinical and immunologic monitoring is not su cient to detect virologic failure in a timely manner [32][33][34], which further supports the need for viral load testing as a strategy to monitor response to treatment in children. This is similar to ndings from a study done in Uganda and Zimbabwe, the ARROW TRIAL which highlighted the importance of con rming virological failure before switching to second-line ART, since some children with detectable low-level viraemia spontaneously resuppressed [35].…”
Section: Discussionsupporting
confidence: 87%
“…Our ndings are in agreement with previous Sub-Saharan Africa studies which have shown that clinical and immunologic monitoring is not su cient to detect virologic failure in a timely manner [32][33][34], which further supports the need for viral load testing as a strategy to monitor response to treatment in children. This is similar to ndings from a study done in Uganda and Zimbabwe, the ARROW TRIAL which highlighted the importance of con rming virological failure before switching to second-line ART, since some children with detectable low-level viraemia spontaneously resuppressed [35].…”
Section: Discussionsupporting
confidence: 87%
“…There appear to be limited data on the incidence of viral blips in children in the low-income setting (Jobanputra et al, 2015;Szubert et al, 2017). In a retrospective analysis of VL tests among children who initiated ART in Uganda and Zimbabwe, 46% of children experienced viral blips (Szubert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be limited data on the incidence of viral blips in children in the low-income setting (Jobanputra et al, 2015;Szubert et al, 2017). In a retrospective analysis of VL tests among children who initiated ART in Uganda and Zimbabwe, 46% of children experienced viral blips (Szubert et al, 2017). This is considerably higher than the results of the present study, but may be explained by the use of WHO 2006 criteria for ART initiation, which relied on clinical and/or immunological assessment and not just the diagnosis of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects received first-line ART regimen according to Chinese guidelines for diagnosis and treatment of HIV/AIDS [26]. This included two nucleoside reverse transcriptase inhibitors (NRTIs) and a non-nucleoside reverse transcriptase inhibitor (NNRTI) that are widely used globally [27][28][29][30][31]. All participants were followed up every 3 to 6 months for evaluation of VL, CD4 + T cell counts, and other routine clinical parameters.…”
Section: Study Populationmentioning
confidence: 99%